Diversity and Selection of Surface Marine Microbiomes in the Atlantic-Influenced Arctic - Aalto, Nerea J.; Schweitzer, Hannah D.; Krsmanovic, Stina; Campbell, Karley; Bernstein, Hans C. (Frontiers in Microbiology, 2022)
Arctic marine environments are experiencing rapid changes due to polar amplification of global warming. These changes impact the habitat of the cold-adapted microbial communities, which underpin biogeochemical cycles and marine food webs. We comparatively investigated the differences in prokaryotic and microeukaryotic taxa between summer surface water microbiomes sampled along a latitudinal transect from the ice-free southern Barents Sea and into the sea-ice covered Nansen Basin to disentangle the dominating community (ecological) selection processes driving phylogenetic diversity. The species composition and richness of each site-specific microbiome was assessed in relation to physical and biogeochemical conditions of the environment. Strong homogenous deterministic selection processes were inferred across the entire sampling transect via a phylogenetic null modelling approach. The results also suggest that regional phytoplankton blooms are a major prevalent factor in governing the bacterial community structure. Differences in temperature and salinity between study sites did not significantly impact the microbial species richness or community composition. This study supports the consideration that strong homogenous selection is imposed across these cold-water marine environments uniformly, regardless of geographic assignments as either the Nansen Basin or Barents Sea.